NEUROTICISM AND NEGATIVE RELIGIOUS COPING: THE MEDIATING AND MODERATING ROLES OF RELIGIOSITY AND THE IMAGE OF GOD - Trups-Kalne, Ingrīda; Perepjolkina, Viktorija; Lietaviete, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Several studies have found correlations between neuroticism as one of personality traits and used negative religious coping strategies in difficult life situations, which in turn has a negative impact on physical and mental health outcomes. Therefore, it is important to explore the explanatory factors for the association between neuroticism and negative religious coping. This study aims at investigating whether there is a mediator effect of the image of God and a moderator effect of religiosity on the relation between neuroticism and the use of negative religious coping strategies. The group of respondents consisted of 336 Latvian-speaking Roman Catholic adults aged 18 to 86 (M = 44.42; SD = 12.90, 74.9 % women). The data was collected by an online survey with the following instruments: the Brief RCOPE, the God Image Scale, the Latvian Personality Inventory LPAv-3, the Centrality of Religiosity Scale CRS-5 and the Socio-demographic Inventory. The results of this study revealed that the image of God has a partial mediating effect on the relation between neuroticism and negative religious coping. The study also indicated that religiosity is a moderator in relationship between neuroticism and negative religious coping – the higher the degree of religiosity the closer the relation between neuroticism and negative religious coping. The outcomes of the study can be used as basis for religious interventions in psychotherapy, as well as health-care consulting and pastoral counselling aimed at reducing the negative impact of negative religious coping on physical and psychological health.